2018
DOI: 10.1155/2018/5034741
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Amegakaryocytic Thrombocytopenia and Pure Red Cell Aplasia in Thymoma

Abstract: Association of thymoma with myasthenia gravis, pure red cell aplasia, and aplastic anemia is well documented. However, thymoma complicated by acquired amegakaryocytic thrombocytopenia (AAMT) is rarely reported. Here, we present a case of a 60-year-old male with past medical history of recurrent invasive thymoma who presented with cough and blood in sputum. He was found to have severe normocytic normochromic anemia and thrombocytopenia that did not improve with intravenous steroids or multiple transfusions of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Studies have demonstrated that increases in cell count may require different time intervals, besides exhibiting different follow-up times to evaluate disease recurrence. Most patients had an effective response to treatment; however, in two, the response was not described [6,10]. In addition to our study, we were only able to identify one case where a patient underwent allogeneic stem cell transplantation and, in contrast to our case, longterm cure was documented [9].…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Studies have demonstrated that increases in cell count may require different time intervals, besides exhibiting different follow-up times to evaluate disease recurrence. Most patients had an effective response to treatment; however, in two, the response was not described [6,10]. In addition to our study, we were only able to identify one case where a patient underwent allogeneic stem cell transplantation and, in contrast to our case, longterm cure was documented [9].…”
Section: Discussionmentioning
confidence: 67%
“…Two patients were diagnosed with thymoma in the presence of signals and symptoms of myasthenia gravis [2,6], while the other cases reported no systemic abnormalities other than hematologic ones. Regarding hematological progress, in one case aplastic anemia was preceded by immune thrombocytopenic purpura [4] and in three others by the association of pure red cell aplasia and amegakaryocytic thrombocytopenia [6,9,10]. e present case was only preceded by isolated amegakaryocytic thrombocytopenia.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Between these cases, four patients were able to improve their cytopenias whereas in the remaining two cases information about follow‐up were not available and one patient left the hospital few days after therapy initiation . Notably, in three cases including ours PRCA and amegakaryocytic thrombocytopenia (AT) progressed to aplastic anemia despite immunosuppression, thus empowering the theory, previously cited in the other reports, that PRCA and AT may be early presentation of complete aplasia.…”
Section: Discussionmentioning
confidence: 85%